Development of an RT-PCR diagnostic test for an avian astrovirus - Koci, Matthew D (J Virol Methods, 2000)
Astroviruses are small round viruses that cause enteric disease in the young of several species. Detection and diagnosis of astrovirus infection in non-human hosts relies heavily on electron microscopy and fluorescent antibody tests. Recently, our laboratory isolated and sequenced an avian astrovirus from poult enteritis mortality syndrome affected turkeys. These studies describe the development of RT-PCR methods, which specifically detect regions of the viral capsid and polymerase genes, and demonstrate their use in detecting astrovirus infection in commercial turkey flocks.